Emergency Response with Potato and Sweetpotato among drought-affected farmers in SNNPR, Ethiopia - International Potato Center (2018)
The Emergency potato and sweetpotato seed support enabled farmers in the Southern Nations Nationalities and People’s Region (SNNPR) to restore the varieties they lost to a severe drought in 2015/2017, and improve household food and nutrition security. From June 2016 to June 2018, 13,000 direct benefi ciary farmers and over 5,500 indirect benefi ciary farmers got orange-fl eshed sweetpotato (OFSP) vine cuttings, produced over 5,000 metric tons of OFSP roots, and trained 133 crop and nutrition experts and 37,651 farmers on sweetpotato agronomy and nutrition.